Biogeochemical processes accounting for the natural mercury variations in the Southern Ocean diatom ooze sediments - Zaferani, Sara; Biester, Harald (Ocean Science, 2020)
Due to its toxic nature and its high potential for biomagnification, mercury is a pollutant of concern. Understanding the marine biogeochemical cycle of mercury is crucial as consumption of mercury-enriched marine fish is the most important pathway of human exposure to monomethylmercury, a neurotoxin. However, due to the lack of long-term marine records, the role of the oceans in the global mercury cycle is poorly understood. We do not have well-documented data of natural mercury accumulations during changing environmental conditions, e.g., sea surface conditions in the ocean. To understand the influence of different sea surface conditions (climate-induced changes in ice coverage and biological production) on natural mercury accumulation, we used a continuous ∼170 m Holocene biogenic sedimentary record from Adélie Basin, East Antarctica, which mainly consists of silica-based skeletons of diatoms. We performed principal component analysis and regression analysis on element concentrations and corresponding residuals, respectively, to investigate the link between sediment mercury accumulation, terrestrial inputs, and phytoplankton productivity. Preindustrial mercury in the remote marine basin shows extremely high accumulation rates (median: 556 µg m−2 yr−1) that displayed periodic-like variations. Our analyses show that the variations in total mercury concentrations and accumulation rates are associated with biological production and related scavenging of water-phase mercury by rapidly sinking algae or algae-derived organic matter after intense algae blooms. High accumulation rates of other major and trace elements further reveal that, in regions of high primary productivity, settling of biogenic materials removes a large fraction of dissolved or particulate-bound elements from the free water phase through scavenging or biological uptake. The link between mercury cycling and primary production will need to be considered in future studies of the marine mercury cycle under primary production enhancement through ...